Women and states : norms and hierarchies in international society - Towns, Ann E. , 1970- (Cambridge University Press, 2010)
"Momentous changes in the relation between women and the state have advanced women's status around the globe. Women were barred from public affairs a century ago, yet almost every state now recognizes equal voting rights and exhibits a national policy bureau for the advancement of women. Sex quotas for national legislatures are increasingly common. Ann Towns explains these changes by providing a novel account of how norms work in international society"--Provided by publisher